The management of information systems - Dickson, Gary W. (McGraw-Hill Book Company, 1984)
The new edition offers the most current coverage available, including expanded discussions of social networking, IT security, mobile computing, and much more. From overviews of the information age to online business and business intelligence, readers gain a sound balance of the technical and business elements of information technology. In addition, numerous business cases integrated throughout the text enable readers to apply what they learn to real-world practice--equipping them with skills they can immediately put into action in the business world.